The Impact Of Physical Fitness On Acute Mountain Sickness Incidence: A Study At Mount Buthak Batu Malang - Faqih, Moh. Ubaidillah; Sawanurdin, Muhammad Priyo Tegar (INTERNATIONAL JOURNAL OF MIDWIFERY RESEARCH, 2024)
Background: Nowadays, hiking has become a highly favored trend among all groups. What is very much needed before hiking is to ensure that the body is in a healthy condition by maintaining physical fitness. This is because during hiking, the body requires energy to prevent injuries and altitude sickness, also known as Acute Mountain Sickness. Objective: To determine the Relationship between Physical Fitness and Acute Mountain Sickness (AMS) on Mount Buthak, Batu Malang Regency. Method: This study is a non-experimental research using a correlational analytic design with a cross-sectional time approach. The population in this study is 150 climbers with a sample size of 109 climbers using simple random sampling technique. The independent variable in this study is physical fitness while the dependent variable is Acute Mountain Sickness. The instruments used are a physical fitness questionnaire and an Acute Mountain Sickness questionnaire. Data analysis in this study uses Spearman's rho Test with the assistance of SPSS software for Windows version 25. Results: The statistical test results of the relationship between physical fitness and Acute Mountain Sickness obtained a significance value of p < 0.05 which means that H1 is accepted. Conclusion: The statistical test results of the relationship between physical fitness and Acute Mountain Sickness obtained a significance value of p < 0.05 which means that H1 is accepted, thus it can be concluded that there is a relationship between Physical Fitness and Acute Mountain Sickness (AMS) on Mount Buthak, Batu Malang Regency. Most respondents maintain good physical fitness, and half of the respondents experience Acute Mountain Sickness with a mild category.